Dynamic Model and Control of an Electric Vehicle with Four In-Wheel PMSMs - Yıldırım, Merve; Oksuztepe, Eyyup; Kürüm, Hasan (My University, 2024)
In this paper, a dynamic modeling and control of an Electric Vehicle (EV) with four In-Wheel Permanent Magnet Synchronous Motors (IW-PMSM) are realized by using MATLAB/Simulink. In automotive applications especially in the EVs, PMSMs are generally utilized due to significant features such as high efficiency, high power density, and fast torque response. For this reason, they are also preferred in this study. Four PMSMs are fitted into the wheels to distribute power evenly for each wheel and thus, each motor can be controlled independently. In the dynamic model of the EV, all lateral and longitudinal forces acting on the EV are calculated. Besides, four wheel speeds are estimated according to the designed an Electronic Differential System (EDS) based the speed of the vehicle and steering angle. Then, a PID controller is designed so that the difference in the wheel speed values taken from the EDS is equal to the difference in the speeds taken from the actual system. The speed curve of each wheel and the road curve of the EV are drawn for different steering angles. As a result, it is observed that the stability of the EV is provided for various road conditions. Besides, complexity of the system is reduced by the proposed simpler control technique than the other methods in the literature such as fuzzy logic, direct torque control, and sliding mode control.
Keywords: Electric vehicle; dynamic model; permanent magnet synchronous motor; motor control.